Cultivo de la habichuela en zona cafetera - González, H. (International Center for Tropical Agriculture, 1987)
The objectives, advantages, and disadvantages of snap bean cultivation in the coffee-growing area of Colombia are listed. General aspects on cultivation practices, phytosanitary problems, and production costs are mentioned. (CIAT)